Effects of Mn and Sr doping on the electrical properties of lead-free 0.92BCZT-0.08BZT ceramics - Parjansri P. (Taylor and Francis Ltd., 2015)
The effects of Mn and Sr doping on the electrical properties of lead-free 0.92[(Ba0.85Ca0.15Zr0.1Ti0.9)O 3]-0.08[(BiZn0.5Ti0.5)O3] ceramics have been studied. A-site and B-site doping with 0.00-0.05 mol% of SrCO 3 and 0-0.25 mol% of MnO2 was performed. The ceramics were prepared using the solid state reaction technique. The powder was ball-milled for 24 h, then calcined at 1,000C for 4 h and sintering at 1,300C for 2 h. Phase formation and microstructure of ceramics were examined using an x-ray diffractometer (XRD) and scanning electron microscopy (SEM). All samples have a single phase of perovskite structure. Grain size and density value were in the range of 3.43-4.07μm and 5.78-5.83 g/cm3, respectively. The electrical properties of the ceramics were investigated as a function of Mn and Sr doping. It was found that the dielectric constant, activation energy and ac conductivity change with the dopant. Moreover, Mn and Sr doping lead to a decrease of dielectric loss, lower than 0.003 for all samples (at 1 kHz). Copyright© Taylor and Francis Group, LLC.